Further Contribution to the Flora of Mount Abu in Rajasthan - Chohan, J. G.; Shah, G. L.; Patel, R. J. (Indian Forester, 1967)
The present paper is a supplementary list of plants collected from Mt. Abu in October, 1953 and September, 1966. In all about 49 plants are listed.